2021
DOI: 10.1108/jima-09-2020-0305
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 cause-related campaigns and consumers’ purchase intention: does religiosity matter?

Abstract: Purpose This paper aims to propose and test a theoretical framework in which attitude towards COVID-19 cause-related campaigns mediates the effects of identification with the cause, donation size, emotional arousal and subjective norms on consumer purchase intention. The authors also explore the moderating effect of religiosity in an emerging nation marked by the dominance of the Islamic doctrine. Design/methodology/approach Survey data from a sample of 561 consumers from Morocco were analyzed to test the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 69 publications
2
15
0
1
Order By: Relevance
“…Muslim customers are perceptible for the strong influence of religion on their practices, beliefs and behaviors (Chetioui and Lebdaoui, 2021). Prior studies on Muslim consumers have constantly conveyed a significant impact of Islamic religiosity on Muslim consumers’ behavior in different contexts (Abou-Youssef et al , 2015; Ilter et al , 2017; Yeniaras, 2016).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Muslim customers are perceptible for the strong influence of religion on their practices, beliefs and behaviors (Chetioui and Lebdaoui, 2021). Prior studies on Muslim consumers have constantly conveyed a significant impact of Islamic religiosity on Muslim consumers’ behavior in different contexts (Abou-Youssef et al , 2015; Ilter et al , 2017; Yeniaras, 2016).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The accepted value of Cronbach's alpha is 0.7 (Chetioui and Lebdaoui, 2021); however, values above 0.6 are also accepted (Griethuijsen et al, 2015;Taber, 2018) which means that our Cronbach's alpha shown in Table 2 values would be satisfied for each variable as they are all above the accepted value. The third criterion used is the average variance extracted (AVE) which is as in Table 2 above 0.5 for all the constructs which mean that convergent validity was achieved for the case of this research (Hair et al, 2010).…”
Section: Measurement Modelmentioning
confidence: 93%
“…Besides financial wellness, the formation of attitudes and behaviours is largely driven by religion either at the individual or collective level (Chetioui & Lebdaoui, 2021). Indeed, religiosity reflect an individual's belief in God and his keenness to act in accordance to the religion (Abou, Richard, & Noor, 2013).…”
Section: The Determinants Of Philanthropic Behaviourmentioning
confidence: 99%
“…Indeed, philanthropy has play its role in poverty alleviation, realizing the needs of those in need, relieving those in debt and helpless travelers to complete their journey (Abdullahi, 2019;Jamal, Yaccob, Bartikowski, & Slater, 2019). Though mainly motivated by religiosity and the feeling of being humane (Chetioui & Lebdaoui, 2021;Doces, Goldberg, & Wolaver, 2022) research on the determinants of philanthropic behavior during pandemic is scarce. However, during COVID-19 pandemic, various funds have been established collecting plentiful donations within a short period is indeed, applauding.…”
Section: Introductionmentioning
confidence: 99%